1975
DOI: 10.1007/bf01139539
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of malonaldehyde with collagen III. Binding site characteristic of malonaldehyde with respect to collagen

Abstract: In this paper have been studied properties of a product that arose from the interaction of malonaldehyde with collagen. It has been shown by an amino acid analysis that malonaldehyde reacts in a significant way on lysine and tyrosine residues. The partcipation of tyrosine in the reaction with malonaldehyde has been further demonstrated by means of spectrophotometry. It has also been found that the hydrolysis by pronase is considerably modified with the cross linked collagen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1975
1975
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…The low activity of SOD in workers of coal handling unit could be due to inactivation of the enzyme by crosslinking or damage to DNA lipid peroxidation and decreased expression of the enzyme. [26] Coal dust concentration was not measured in this study although there was variable amount of dust in different units. Occupational exposure to coal showed a decrease in all the red blood cell antioxidants in some stages of coal workers’ pneumoconiosis.…”
Section: Discussionmentioning
confidence: 95%
“…The low activity of SOD in workers of coal handling unit could be due to inactivation of the enzyme by crosslinking or damage to DNA lipid peroxidation and decreased expression of the enzyme. [26] Coal dust concentration was not measured in this study although there was variable amount of dust in different units. Occupational exposure to coal showed a decrease in all the red blood cell antioxidants in some stages of coal workers’ pneumoconiosis.…”
Section: Discussionmentioning
confidence: 95%
“…Possible reason could be due to utilization of malondialdehyde in crosslinking of collagen. [ 15 16 ] It has been shown by an amino acid analysis that malonaldehyde reacts in a significant way on lysine and tyrosine residues. [ 16 ] Previous studies have revealed fibroblast stimulating properties of malondialdehyde in culture.…”
Section: Discussionmentioning
confidence: 99%
“…[ 15 16 ] It has been shown by an amino acid analysis that malonaldehyde reacts in a significant way on lysine and tyrosine residues. [ 16 ] Previous studies have revealed fibroblast stimulating properties of malondialdehyde in culture. [ 17 ] Addition of MDA to cultured fibroblasts increased collagen production by 2–3 times.…”
Section: Discussionmentioning
confidence: 99%
“…The composition of collagen is unique among proteins because it contains a high percentage of hydroxy proline which relegates it to the "pleated-sheet" conformation thereby bringing adjacent fibrils into proximity for the formation of intermolecular bonds (76). The formation of adventitious cross-links is associated with lipid peroxidation (77). The formation of malonaldehyde via lipid peroxidation leads to a reactive intermediate which can form aldimine cross-links between adjacent collagen fibrils.…”
Section: Crosslinking Of Collagenmentioning
confidence: 99%